" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a(4) + b = -2
4a + b =-2..........(1)
f(-4) = ax + b = 6
a(-4) + b = 6
-4a + b = 6..............(2)
4a + b = -2
-4a +b = 6
---------------- +
2b = 4
b = 4/2 = 2
4a + b = -2
4a + 2 = -2
4a = -2 -2
4a = -4
a = -4/4 = -1
f(8) = ax + b
= -1(8) + 2
= -8 + 2
= -6 (c)
jadi
f(4) = a(4) + b = -2
4a + b = -2
f(-4) = a(-4) + b = 6
-4a + b = 6
jadi
4a + b = -2
-4a + b = 6
---------------------- +
2b = 4
b = 2
jadi a
4a + b = -2
4a + 2 = -2
4a = -2 - 2
4a = -4
a = -1
jadi f(8) = ax + b =....
-1*8 + 2 = -6
semoga bermanfaat
jadikan jawaban terbaik ya